Pengaruh Kepuasan Kerja, Motivasi, dan Kedisiplinan Terhadap Produktivitas Kerja Karyawan PT. Sinarmas Multifinance di Surakarta - Mayasari, Ratih; Hendratmoko, Christiawan (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
This research  was carried out on PT. Sinarmas Multifinance in Surakarta.  The aim  of  the  study  are:    (1)  To  know  the  influence  of  work  satisfaction,  motivation,  and discipline  toward  productivity.    (2)  To  know  the  dominant  factor  among  work satisfaction, motivation, and discipline that influence toward productivity. The  hypothesis  drawnare:  (1)  Presummed  that  there  are  influence  of  work satisfaction,  motivation,  and  discipline  toward  productivity.    (2)  Presummed  that motivation has dominant influence toward productivity. The population of this research is 49 employees of PT. Sinarmas Multifinance in Surakartawith  primary data. Technique of Analysis applied are validity test, reliability test, multiple linear regression, t-test , F- test and coefficient of determination. The  results  of  this  study  are:    (1)  There  are  simultaneous  and  significant influence  of  work  satisfaction,  motivation,  and  discipline  toward  productivity.    (2) Motivation  has  dominant  influence  toward  productivity  in  PT.  Sinarmas  Multifinance, Surakarta